The Registration Of “Ulayat”’ Land In West Sumatra: Between The Legal Certainty And The Social Justice - A. Yoma Amanda Putri; Yuke Sinayangsih; Djauhari Djauhari (Jurnal Akta, 2018)
Ulayat land House of communal rights is a member of the House, as a fellowship of customary law. The purpose of the arrangement of Ulayat Land is to protect the customary land and take the benefits for survival in some generations and uninterrupted between the members of the House with its territory. Conceptually, this is related to a social justice. While the purpose of the registration of land, according to the article 19 BAL is to guarantee the legal certainty over land. The implementation of Customary Land or Ulayat Land Registration was preceded by the creation of the base rights. The making of the pedestal of this right in the form of a waiver of physical mastery of plots of land (Sporadic). Before the creation of the pedestal of this right was preceded by the creation of Ranji by Ninik Mamak, which was passed by the House. The writing Empirical Juridical approach, was supported by empirical juridical approach. Empirical juridical approach was done by collecting all the materials and data obtained from the field-related to the problems are examined. Registration of the customary (Ulayat) rights of the House is done by applying to the Head Office of land district/city. The filing listed on behalf of or Mamak Head Heirs using a waiver of physical mastery of parcels of the land that are signed by the Mamak Head Chiefs as Heir. The statement must be approved by the head of the tribe or Tribal King and Chairman of custom Density Nagari and known by Lurah/village chief concerned by attaching a document containing the names of the members of the House of at least three generations created by Mamak Chief Heir and known by the ruler of the tribe and the leader of the RIGHT. The registration of Customary House was expected to guarantee legal certainty for members of the House as a fellowship of customary law, because it is aimed at maintaining Customary Rights for indigenous Justice. Therefore, the customary land register of House in conceptional in touch with the land registry purposes, i.e. to guarantee legal certainty while also embodying a sense of Justice for indigenous citizens (members of the House). Keywords: Social Justice; Legal Certainty; The Registration of Ulayat Land.